Missed opportunities to provide sexually transmitted and blood-borne infections testing in British Columbia: An interpretive description of users’ experiences of Get Checked Online's design and implementation - Ihoghosa Iyamu; Rosemin Kassam; Catherine Worthington; Daniel Grace; Heather Pedersen; Devon Haag; Mark Bondyra; Amy Salmon; Mieke Koehoorn; Mark Gilbert (Digital Health, 2024)
Background Digital testing services for sexually transmitted and blood-borne infections (STBBIs), such as GetCheckedOnline, experience significant user drop-offs. For example, 32% of GetCheckedOnline users needing testing at account creation do not test, constituting missed opportunities. We explored the influence of users’ expectations and experiences of GetCheckedOnline's web design and implementation on missed opportunities. Methods This interpretive description purposively sampled 14 GetCheckedOnline users who created accounts between April 2022 and February 2023, indicated needed testing at account creation but did not test. We conducted semi-structured interviews and cognitive walkthroughs of GetCheckedOnline on Zoom, exploring participants’ expectations and experiences, including problems using the service. Interviews were audio recorded, transcribed verbatim, and analyzed using reflexive thematic analyses. Results Three themes were identified: (a) transitioning between GetCheckedOnline and laboratory services is a major testing barrier; (b) users’ appraisal of their health and social contexts is a determinant of testing through GetCheckedOnline; and (c) tailoring GetCheckedOnline's design and implementation to accommodate varying user needs can promote equitable testing. Health equity issues occurred along sociodemographic gradients as the GetCheckedOnline-laboratory transition was more onerous for older users. Users’ appraisal of their testing needs which varied by age and gender, and their assessment of time, and travel requirements for testing in remote communities influenced testing. Learning about GetCheckedOnline from healthcare providers improved testing compared with learning about the service through Google search which raised trust concerns regarding GetCheckedOnline's authenticity. Suggested improvements to promote health equity include personalized education, mail-in testing options, and simpler seamless web experiences. Conclusions To promote equitable access to digital STBBI testing services such as GetCheckedOnline, we can adapt web-design and implementation to suit user needs and contexts, ensuring simplicity and options for testing that reduce user burdens.